(3TQM bUjOI GdbUU GdMb aj eOM NjQ GdNdbs - (3eMeO Hf jMji HgQGfs; (3jMji Hf TQa GdOjf Hf TeS GdOjf Hf GdegOj dOjf Gddg CMeO Hf jMji Hf GdeQJVjs ((3eOQSI UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi EUWai SjOfG eMeOkG ef CTQa GdYfGUQ , haVdg Ydi LejY GdChGFd hGdBNQ , hCfRd eOMg ai GdbQBf s
(3BNQgG (B:s
(3hGdCjc , GdTLQ GdedJa hGMOJg Cjcg aQZ ef Qbe gPG GdTQM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3cJHJ CHjGJ GdbUjOI HGdMeQIs
(3cJHJ HCeQ CejQ GdeDefjf UGMH GdbUjOI hYfGjI GdbGVi Ydi Hf YHO Gddg Hf Ydi Hf QhGYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdCOHs